P191 Robotic Surgery shows significant promise in delivering superior outcomes for patients with Inflammatory Bowel Disease. (30th January 2023) - Karri, R; Grewal, C; Yassin, N
Abstract: Background: Robotic surgery is a relatively novel surgical advancement in minimally invasive surgery for patients with Inflammatory Bowel Disease (IBD). The pathophysiology of the disease inherently makes these surgeries more complex with high complication rates. This study aimed to the evaluate the efficacy of robotic procedures for such patients and compare the short-term outcomes with laparoscopic surgery in patients with IBD. Methods: A retrospective review was conducted of all patients who underwent robotic and laparoscopic surgery for IBD between November 2018 and April 2022 at a single institution. Demographics, peri-operative, intra-operative and post-operative data were analysed. Results: 24 robotic cases were performed in the time period (75% Crohn's) whilst 18 cases were performed laparoscopically (39% Crohn's). Majority of the robotic patients had a Right Hemicolectomy (63%) with stoma formations in 38% of the procedures. 44% of the laparoscopic patients had a Total Colectomy and 39% had a Right Hemicolectomy with 78% of them having stomas. There was no significant difference in the patients age or BMI with a median age of 30 and BMI of 24.1 in the laparoscopic surgeries and a median age of 36 and BMI of 24.8 in the robotic group. The median operative time for the laparoscopic procedures was longer with 250 minutes versus 220 minutes in the robotic patients. The length of hospital stay for the patients was also greater for laparoscopic patients with a median of 9 compared to 6 days for robotic patients. 3 patients necessitated return to the ward within 30 days after laparoscopic surgery (17%) compared to only one robotic case (4%). However, 2 patients had a Clavin Dindo Grade 3 complication after robotic surgery compared to one in the laparoscopic set. In both sets of patients, one patient required surgery within 30 days: the robotic patient requiring laparotomy for adhesion-lysis and the laparoscopic patient for wound closure post wound dehiscence. Zero cases across all the patients necessitated conversion to open surgery and the mortality rate was 0%. Conclusion: The results of this single centre study provide further support to studies demonstrating the feasibility and efficacy of robotic surgery in IBD patients. Patients operated robotically had a comparable safety profile with a similar complication rate whilst having whilst having shorter operating times and shorter length of hospital stay. Length of stay in hospital is a surrogate marker for early recovery post-surgery and carries significant benefit in the modern-day demand for hospital bed spaces. Therefore, robotic surgery offers a potentially superior alternative in minimally invasive surgery.